The role and place of computational experiments in the study of celestial mechanics - Мукушев , Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article deals with the implementation of computational (computer) experiments on the movement of spacecraft near the Earth. The main stages Of the computational experiment are identified and analyzed. This experiment is used to study physical objects and phenomena. The issues of Creating physical, mathematical and computer models of the objects Under Study Are considered. The conditions of physical modeling are disclosed. Physical modeling is implemented in the conditions of idealization, formalization and abstraction of physical objects and processes. In mathematical modeling, a numerical analysis of the object under study and The construction of a mathematical model are carried out. At the stage Of computer modeling, software is created. This program is necessary for solving mathematical equations. As a programming language, you can use Microsoft Excel, mathcad, Pascal, C++ , Python, etc. The article presents the method of using the program in the mathcad language. The program in the mathcad environment is designed to study the flight of spacecraft in various initial conditions. The following initial conditions of spacecraft motion near the Earth are considered: the satellite moves in a circular and elliptical orbit; the ship starts from the Earth’s surface at the second cosmic speed; the rocket takes off from the Earth’s surface at an angle of 45 degrees to the horizon